The Effect of Social Networks on the Improvement of Saudi EFL Students - AlQahtani, Najla Abdulrahman (Journal of Humanities & Social Sciences, 2018)
The overwhelming use of social networks amongst the new generation and their spectacular growth enables EFL students to use the language outside the classroom and in everyday life routines. Since traditional language learning has its flaws and limitations in improving EFL students, as it decreases the chances of using the language outside the classroom, it is crucial to adopt an up-to-date methodology which enables EFL students to use the language outside the classroom. The main concern of this study was to shed light on the usefulness of social networking sites to improve EFL students. The study was conducted using a sample of 45 randomly chosen female EFL university students, at Salman Bin AbdulAziz University in  Alkharj, Saudi Arabia. All the participants, whose ages ranged from 18 to 24 years, subscribed to a minimum of one social network. Data was collected through a 23 questions questionnaire.  Students showed a positive attitude towards using social networks in language learning. The study verified that social networks are meaningful means which can improve the students’ language and promote their academic knowledge and skills.
Keywords: social networks; EFL; language learning